Risk Factors for Cerebral Hyperperfusion Syndrome After Combined Revascularization in Adult Patients with Moyamoya Disease - Xu, Dongxiao; Guo, Jiaojiao; Zheng, Bingjie; Wu, Qiaowei; Gareev, Ilgiz; Beylerli, Ozal; Beilerli, Aferin; Shi, Huaizhang (Current neurovascular research, 2024)
Cerebral hyperperfusion syndrome (CHS) is known as a complication after bypass surgery for Moyamoya disease (MMD). However, the incidence of CHS has not been accurately reported, and there is no consensus on the risk factors associated with it. The aim of this study was to determine the risk factors associated with postoperative CHS after surgical combined revascularization used to treat adult patients with MMD. To assess the frequency and characteristics of CHS in patients with MMD after revascularization operations. Patients who received combined revascularization from Jan 2021 to Nov 2022 were retrospectively reviewed. Preoperative clinical characteristics and radiographic features were recorded. Postoperative CHS after surgery were examined. Multivariate logistic regression analyses were performed to identify the risk factors for CHS. A total of 133 patients (141 hemispheres) were included in this study. Postoperative CHS were observed in 28 hemispheres (19.8%), including focal cerebral hyperperfusion syndrome (FCHS) in 20 hemispheres (14.2%), hemorrhage in 4 (2.8%) hemispheres, seizures in 4 (2.8%) hemispheres. The results of multivariate logistic regression analysis indicated that preoperative hypertension (OR 4.705, 95% CI 1.323 ~ 12.554, p = 0.014), cerebral hemorrhage onset (OR 5.390, 95% CI 1.408 ~ 20.642, p = 0.014) and higher Hct level (OR 1.171, 95% CI 1.051 ~ 1.305, p = 0.004) were significantly associated with CHS after combined revascularization. Preoperative hypertension, cerebral hemorrhage onset, and higher Hct level were independent risk factors for CHS after combined revascularization.